European Parliament resolutions—effective agenda setting or whistling into the wind?. Issue 3 (3rd April 2019) - Kreppel, Amie; Webb, Michael
ABSTRACT: The European Parliament is one of the most studied legislatures in the world. The general consensus in most of these analyses is that the power of the EP in the legislative processes of the EU has increased precipitously, since the introduction of the co-decision procedure. One continuing perceived weakness of the EP, however, is its inability to introduce new legislation. While the EP can request that the Commission initiate a proposal, it lacks the power to introduce bills itself. This research looks at the indirect agenda power of the EP through an analysis of EP own initiative resolutions and their impact on the policy agenda of the EU. The research introduces anew dataset on all EP resolutions between 2000 and 2015 and compares the pre- and post-2009 period to assess the impact of formal treaty changes to the legislative role of the EP have had on its agenda-setting capacity.